Inhibitory actions of loperamide on absorptive processes in rat small intestine. Issue 6 (June 1986) - Hardcastle, J; Hardcastle, P T; Cookson, J
Abstract : Mucosal loperamide caused a dose dependent reduction in the absorption of actively transported hexoses and amino acids, together with the associated rise in short circuit current. Na+ and fluid movement were also inhibited. Serosal application of the drug was without effect on these processes. The passive movement of fructose across the gut was not affected by loperamide which is therefore unlikely to act by reducing tissue permeability. In low Na+ conditions the inhibitory actions of loperamide on glycine absorption were reduced. Loperamide reduced basal Na+ transport although it did not affect the stimulation of Na+ absorption caused by mannose. Loperamide had no effect on the total ATPase activity nor on the Na+, K+-ATPase activity of mucosal homogenates. The effects of loperamide were not mimicked by morphine nor were they antagonised by naloxone and hence do not seem to involve an opiate receptor. It is concluded that loperamide exerts its inhibitory effects by an interaction with the Na+ sites of the nutrient carriers.